A Study of the Dialogic Dimension of Critical Thinking in Medical Students at the Antonio Nariño University (Papeles, 2021)
Research on critical thinking and the different areas that make them, it up today represent a challenge, due to the great variability of concepts and interpretations according to the authors and the multiple components, approaches and types of studies that “per se” this allows to develop. The great diversity of investigative approaches to critical thinking has allowed studies to target diverse populations, mainly in educational settings, the majority of these studies being in the context of evaluating the learning processes, in which aspects are involved. such as in which there are involved aspects such as educational methodologies, the preparation of teachers on critical thinking, teaching strategies, among others, which represent a set of tools necessary for the promotion and development of critical thinking in students.
Keywords: critical thinking; dialogical dimension; education